Toxy noxy foresty forest. 1 - Segawa, Noboru (Toxy Noxy Foresty Forest, 2026)
Papa, Mama...please watch over me. With these two hands, I'll avenge you...! Once upon a time, a happy, cheerful village full of loving, joyous mushrooms lived deep in the forest. Everything was wonderful and splendid and bright-until the day he came. Bringing death and destruction wherever he went, the malignant, miasmic mushroom massacred the entire village for no apparent reason. And so began our heroine's journey to bring about the foul fungus's demise...